Genetic Effects on the Gut Microbiota Assemblages of Hybrid Fish From Parents With Different Feeding Habits - Li, Wuhui; Liu, Junmei; Tan, Hui; Yang, Conghui; Ren, Li; Liu, Qingfeng; Wang, Shi; Hu, Fangzhou; Xiao, Jun; Zhao, Rurong; Tao, Min; Zhang, Chun; et al. (Frontiers in Microbiology, 2018)
Gut microbiota play critical roles in host nutrition and metabolism. However, little is known about the genetic effects on the gut microbiota assemblages because a suitable model for investigation is lacking. In the present study, we established the reciprocal hybrid fish lineages derived from the parents with different feeding habits, namely, herbivorous blunt snout bream (Megalobrama amblycephala, BSB, 2n=48) and carnivorous topmouth culter (Culter alburnus, TC, 2n=48). We investigated the genetic effects on gut microbiota assemblages by using 16S rRNA gene sequencing. The results showed that the gut characteristics (structure, relative gut length, relative gut mass, and Zihler’s index) differed between the two types of hybrids and the two parents. In particular, a strong correlation between genotype and gut microbial assemblages indicated that host genetic (subgenome) significantly altered the gut microbiota communities. In addition, the microbial structures (composition and abundance) in the two types of hybrids were more similar to those in BSB parent (P>0.05) than to those in TC parent (P<0.05), and the cellulase contents in the gut (produced by gut microbes) also showed the similar results. The results suggested that the host genomic interaction (mainly subgenome domination) had a sizeable effect on shaping the gut microbiota assemblages in reciprocal hybrid fish. This study enriches our understanding of the relationship between host genetic and gut microbiota assemblages, and provides insight into gut microbiota and metabonomics.